COMPONENTS OF PHENOTYPIC VARIANCE AND HERITABILITY OF EARLY VIGOUR TRAITS OF BREAD WHEAT UNDER CONTRASTING WATER REGIMES - Blažić, Milica (Journal of Agricultural Sciences (Belgrade), 2025)
Exploring drought-tolerance potential and phenotypic plasticity at early stages of development in root system architecture could be crucial in regard to breeding for drought resistance and for selecting wheat ideotypes under climate change. A total of 11 genotypes from the collection of 101 bread wheat genotypes, originating from Serbia and 16 different countries of the world, with desirable traits in terms of increased tolerance to drought, were chosen for parents and eight crosses were performed. Genotypes from P and F1 generations were grown in hydroponic cultivation under polyethylene glycol 6000-induced osmotic stress. The objective of this research was to assess components of phenotypic variance and heritability in a broad sense of early vigour traits (nine root and shoot traits) of bread wheat genotypes in induced drought stress vs. control, in order to choose appropriate traits for breeding for drought resistance. The effect of the genotype was higher on the variability of the tested root traits (46.6%), compared to the tested shoot traits (25.5%). meaning that the root traits can be taken as a more reliable criterion for selection for drought tolerance compared to the investigated shoot traits. Heritability in a broad sense was high (> 82%) for most of the tested traits (primary root length, number of seminal roots, total seminal root length, angle of seminal roots, shoot length, the ratio root dry mass to shoot dry mass), with low genotype × environment interaction (< 20% of total variation) and breeding for drought tolerance should be focused on these traits.
Keywords: Triticum aestivum L., drought stress, root system architecture, shoot traits, seedlings, heritability in a broad sense, components of phenotypic variance.